SUBSTRATOS E ADUBAÇÃO FOLIAR COM BIOFERTILIZANTE NA PRODUÇAO DE MUDAS DE MARACUJAZEIRO E MAMOEIRO - Barros, Cristiane Muniz Barbosa (2011)
Orchards depend on seedlings, whose costs and quality are influenced by substrate and fertilization. The study evaluated nutrition and growth of seedlings of yellow passion fruit and papaya, formosa and solo, in substrates with green manure (GM) composts and under foliar spray of supermagro. Between december 2009 and march 2010, a greenhouse experiment was conducted at the Agronomy Department of South Central State University, Guarapuava, Paraná, in random blocks with split-plots design. Plots received or not foliar application of supermagro. Subplots consisted of substrates: soil; soil + fermented cattle manure; soil + cattle manure composted with black oats; soil + cattle manure composted with ryegrass; soil + cattle manure composted with turnip; and soil + cattle manure composted with vetch. Three seeds were used for each plastic bag filled with substrate. Ten days after emergence (DAE) thinning and the first of three foliar fertilizations were performed. At 50 DAE, growth indicators were determined and the plants were chemicaly analysed for nutrient contents, using the dry mass of the seedlings to calculate N, P, K, Ca, Mg, Cu, Mn and Zn accumulation. Data were submitted to analysis of variance and means compared by Tukey test ( = 0,05). The substrate soil + fermented cattle manure promoted the best seedlings fomation of yellow passion fruit. The substrates soil + cattle manure composted with ryegrass, soil + cattle manure composted with vetch soil + fermented cattle manure were the best substrates to the growth indicators to the papaya formosa and solo. The foliar fertilization with supermagro caused lower growth to the plants.